Analysis of the Application of "SME Accounting" in the Preparation of Financial Reports - Erdita Putri Setyoningrum; Khojanah Hasan; Indah Dewi Nurhayati; Irfan Fatoni (Journal of Management Research and Studies, 2024)
MSMEs are a major milestone in supporting the Indonesian economy, but with the advantages that MSMEs have, MSME actors must also have financial reports that can be accounted for, so that the management of their business operational activities can run well, so that the business they run can remain sustainable. The SME accounting application is present in the digital era which can facilitate MSME players who find it difficult to prepare financial reports, so that by applying their business operational records to the SME accounting application, MSME players can make financial reports in accordance with generally accepted accounting standards. The aim of the research is to find out how the application of SME accounting applications can help SMEs in preparing financial reports for herbal medicine companies in the city of Malang, namely CV. Bagoes Herb. The research method used by researchers is descriptive qualitative in the form of observation, interviews and documentation. The research results show that SME accounting applications can help in preparing CV financial reports. Herba Bagoes, however, there are obstacles faced when implementing the SME accounting application which are caused by several factors, but by recording financial reports using the SME accounting application, the resulting financial reports can be of added value to the company and the financial reports will be accurate, effective and transparent.